2017
DOI: 10.1016/j.juro.2017.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bacillus Calmette-Guérin Strains for Treatment of Nonmuscle Invasive Bladder Cancer: A Systematic Review and Network Meta-Analysis

Abstract: Bacillus Calmette-Guérin strains exhibited significant differences in efficacy compared to chemotherapy. However, no definitive conclusions could be reached regarding strain superiority, and head-to-head trials are greatly needed to further understand the importance of strain selection in determining bacillus Calmette-Guérin efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 24 publications
0
54
0
Order By: Relevance
“…In recent meta-analysis it was concluded, that BCG strains exhibit significant differences in efficacy compared to chemotherapy; however, no definitive conclusions could be reached regarding strain superiority [15,16]. Similar conclusions may be drawn from earlier meta-analysis conducted by the EORTC group [17].…”
Section: Discussionmentioning
confidence: 88%
“…In recent meta-analysis it was concluded, that BCG strains exhibit significant differences in efficacy compared to chemotherapy; however, no definitive conclusions could be reached regarding strain superiority [15,16]. Similar conclusions may be drawn from earlier meta-analysis conducted by the EORTC group [17].…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, the effect of specific BCG strains could be modified by the use of maintenance therapy. 48 This analysis showed that the BCG strains exhibited significant differences in efficacy compared with chemotherapy. 47 Without maintenance, Connaught was more effective than TICE only for the time to first recurrence (hazard ratio 48, 95% CI 1.20-1.82, P < 0.001).…”
Section: Different Clinical Outcomes Afforded By Bcg Strainsmentioning
confidence: 98%
“…Boehm et al carried out a systematic review and network meta-analysis of trials evaluating BCG strains for the treatment of NMIBC against all possible comparators (different BCG strains, chemotherapy and non-BCG biological therapies) with intravesical chemotherapy as the common comparator ( Table 2). 48 This analysis showed that the BCG strains exhibited significant differences in efficacy compared with chemotherapy. However, in the network meta-analysis, no BCG strain showed significant superiority at preventing recurrence compared with any other strain.…”
Section: Different Clinical Outcomes Afforded By Bcg Strainsmentioning
confidence: 98%
See 2 more Smart Citations